Mount Sinai's Center for Stress, Resilience and Personal Growth as a model for responding to the impact of COVID-19 on health care workers. (November 2020) - DePierro, Jonathan; Katz, Craig L.; Marin, Deborah; Feder, Adriana; Bevilacqua, Laura; Sharma, Vansh; Hurtado, Alicia; Ripp, Jonathan; Lim, Sabina; Charney, Dennis
Abstract: The COVID-19 pandemic is anticipated to have a prolonged adverse mental health impact on health care workers (HCWs). The supportive services implemented by the Mount Sinai Hospital System in New York for its workers culminated in the founding of the Mount Sinai Center for Stress, Resilience, and Personal Growth (CSRPG). CSRPG is an innovative mental health and resilience-building service that includes strong community engagement, self- and clinician-administered screening, peer co-led resilience training workshops, and care matching. The long-term sustainability of similar programs across the United States will require federal funding.